Comparative Evaluation of Sealing Ability, Bond Strength, and Antimicrobial Properties of Endodontic Sealers: An In Vitro Study - V Vijith; Anarasi Mahaprasad; A Purusothaman; Aravind Kumar Duraivel; Mariea Francis; Hitesh Chohan (Journal of Pharmacy and Bioallied Sciences)
Objective: To compare the sealing ability, bond strength, and antimicrobial properties of BioRoot root canal sealer (RCS), TotalFill Bioceramic (BC), EndoSeal Mineral Trioxide Aggregate (MTA), and AH Plus in endodontic therapy. Methods: Eighty single-rooted human teeth were divided into four groups (n = 20). Sealing ability was assessed via dye penetration, bond strength with push-out tests, and antimicrobial properties using agar diffusion tests against Enterococcus faecalis. Statistical analysis involved one-way ANOVA and Tukey’s Honestly Significant Difference (HSD) tests (P < 0.05). Results: BioRoot RCS showed the best sealing ability, highest bond strength, and largest antimicrobial zone. AH Plus had the poorest performance. Conclusion: BioRoot RCS is a superior endodontic sealer.